2018
DOI: 10.4103/nmj.nmj_151_18
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, attitude and knowledge regarding oral health among pregnant women: A comparative study

Abstract: Background: Pregnancy in a woman's life is associated with many physiological changes in the body due to alterations in the hormone levels. These altered hormonal levels are associated with many systemic diseases. The incidence of oral diseases in general and periodontal diseases in particular are higher in pregnant women, with gingivitis and periodontitis being the most common. Furthermore, it has been evidenced in literature that periodontal diseases are associated with adverse pregnancy outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…Of all participants, 6506% think there is a link between oral health and pregnancy health, only 8% of all studied sample know that the presence of gingivitis during pregnancy may lead to premature labor or the birth of a low-weight baby, and 35.8% think that pregnancy cause gingivitis. Comparable results were reported in previous literature, [13] reported that all the study participants (100%) in both the groups were aware of the importance of the oral health in overall general health during pregnancy. The results were comparable to a study by [14], in which 81.50% of the study individuals felt that importance should be given for oral health as a part of general health during pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…Of all participants, 6506% think there is a link between oral health and pregnancy health, only 8% of all studied sample know that the presence of gingivitis during pregnancy may lead to premature labor or the birth of a low-weight baby, and 35.8% think that pregnancy cause gingivitis. Comparable results were reported in previous literature, [13] reported that all the study participants (100%) in both the groups were aware of the importance of the oral health in overall general health during pregnancy. The results were comparable to a study by [14], in which 81.50% of the study individuals felt that importance should be given for oral health as a part of general health during pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…The present study showed the importance of oral health care knowledge and behaviors before pregnancy. The results of cross-sectional studies around the world have also highlighted the lack of oral health knowledge among pregnant women [ 42 – 44 ]. Accordingly, some clinical trials have suggested that proper education methods for women before pregnancy can significantly increase their oral health knowledge and consequently improve their oral health status during pregnancy [ 45 – 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some women have knowledge about the relation of PD to adverse pregnancy outcomes, only 47% of them received a diagnosis of oral health or appropriate treatment [ 12 ]. All of these data suggest that there is a need for the education of women in the pregnancy period about PD and its consequences, due to general poor knowledge [ 14 , 15 ].…”
Section: Epidemiology Of Periodontal Disease (Pd)mentioning
confidence: 99%